Development of pictorial asthma action plan - Theng, Cheong Ai; Ying, Lim Poh; Mohamad, Fadzilah; Salim, Hani Syahida; Shariff Ghazali, Sazlina; Lee, Ping Yein; Hussein, Norita; Hanafi, Nik Sherina; Ramdzan, Siti Nurkamilla; Ramli, Rizawati; Tan, Siow Foon; Nordin, Norasnita; et al. (Family Medicine Specialist Association (FMSA) of Malaysia, 2024)
Asthma action plans are used to support selfmanagement and have been shown to improve clinical outcomes. Pictorial asthma action plans (PAAP) have the potential to benefit all patients regardless of their health literacy. We aimed to develop a culturally tailored PAAP to support patient selfmanagement.